MORPHOLOGICAL CHARACTERISTICS OF TERRESTRIAL ORCHIDS IN THE FOREST OF BUKUM VILLAGE , SIBOLANGIT DISTRICT, DELI SERDANG REGENCY - Dwi Indriany; Wina Dyah Puspita Sari; Yusran Efendi Ritonga; Mhd Yusuf Nasution (Universitas Negeri Medan, 2023)
The study aims to determine the types of terrestrial orchids that exist in the Forest of Bukum Village, Sibolangit District, Deli Serdang Regency. This study uses an exploratory method. Orchid found identified and observed morphology from root to fruit. Type 15 species of orchids were found including Anoectochilus longicalcaratus J.J.Sm., Anoectochilus reinwardtii Blume, Calanthe triplicata (Willemet) Ames, Chrysoglossum ornatum Blume, Corymborkis veratrifolia (Rein.w) Blume, Cymbidium ensifolium (L.) Sw., Cystorchis stenoglossa Schltr, Habenaria sp, Hetaeria oblongifolia Blume, Liparis rheedei Lindl, Malaxis oculata (Rchb.f.) Kuntze, Malaxis ophrydis (J.Koenig) Ormerod, Phaius callosus (Blume) Lindl, Phaius corymbioides Schltr, Plocoglottis javanica Blume. 7 species of which have pseudobulbs.